POSSIBILITIES OF A COLLEGIAL SUPPORT GROUP FOR IMPROVING THE PROFESSIONAL CONPETENCES OF TEACHERS DURING REMOTE WORK - Kāposta, Iveta; Sautiņš, Nils (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
In educational institutions, collegial support groups as the form of pedagogical work have long been known and have been incorporated into the system of the organization of methodological work. These are mainly administratively formed long-term activity groups. This study focuses on the less studied so far freely formed short-term activity groups in an educational establishment. The analysis of the activities of the above-mentioned groups as a whole highlight their capabilities in remote working conditions. The study is based on literature analysis and pooling and analysis of structured interview data. The structured interview was designed to find out whether and how teachers come together in groups during remote work, to solve problems that have arisen during the work and what results this work has given. The study concluded that the remote activities of the collegial support group are successful, provided that the educational institution already has a sufficiently long tradition of organizing these groups.